Pentingnya Literasi Budaya Dan Kewarganegaraan Pada Siswa Sekolah Dasar Di Era Globalisasi - Ari Sujarwadi; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the time of progressively progressed globalization, each individual high priority a solid comprehension of managing different societies and identities. Primary school is the ideal spot to collect this view all along. Social and urban proficiency alludes to a comprehension of different parts of culture and city values, as well as the capacity to relate in a genuine manner with individuals from different social layers. Making and reinforcing instructive improvement is a significant part in the endurance of a country in the period of globalization. Particularly as far as creating 21st century abilities and growing productive members of society, expanding education will augment HR.